Ratio Legis of Article 12 Letter F : The Extortion in Corruption - Rahmatina Putri, Izzati; Ismail, Kautsar (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Corruption crimes encompass a variety of offences, one of which is the Extortion Offence. Extortion offences involve offenders proven to demand, receive, or withhold payments through force or threats on material matters while performing their duties as certain officeholders. In Indonesia, regulations for corrupt acts involving extortion offences are outlined in Article 12 letter f of Law Number 20 of 2001, amending Law Number 31 of 1999 on the Eradication of Criminal Acts of Corruption, as well as Article 425 paragraph (1) of the Indonesian Criminal Code. The extent to which a person is considered to have committed a corrupt act involving extortion is a crucial aspect of corruption offences. This study employs the Normative Research Method utilizing statutory and conceptual approaches, with legal material analysis conducted through descriptive means. The findings show that significance of Article 12 letter f in the Corruption Eradication Act as an extension and lex specialist in Article 425 paragraph (1) of the Criminal Code. Officials can take measures to prevent such misconduct to avoid improper cash handling or extortion by those in positions of authority over them. This study offers an in-depth study of illegal levies in corruption, emphasizing Article 12 letter f of Law Number 20 of 2001, aiming to bridge the gap of previous studies and provide practical insights for law enforcement in anti-corruption efforts in Indonesia through normative legal research.